Lithium batteries and electrical devices
By forming an amorphous alloy coating and a porous ceramic layer on the positive electrode current collector of a lithium battery, and using a locally high-concentration or gel quasi-solid electrolyte, the thermal stability problem of high-nickel ternary lithium batteries was solved, thereby improving the safety and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202611255112.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-11-03
AI Technical Summary
High-nickel ternary lithium batteries have poor thermal stability and are prone to thermal runaway due to chain exothermic reactions caused by thermal or electrical abuse. Existing safety technologies have limited effectiveness in improving safety and poor compatibility among components.
A stable positive electrode structure is formed by using an amorphous alloy coating current collector, a porous ceramic layer, and a locally high-concentration or gel quasi-solid electrolyte. Combined with an oxide solid electrolyte and a lithium-ion conductor, a passivation layer with both physical and chemical stability is constructed to optimize the ion transport network.
It effectively prevents heat spread, eliminates hotspots and ignition sources, improves battery safety and electrochemical performance, enhances cycle stability and safety under high voltage, and is suitable for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium batteries, and more particularly to a lithium battery and an electrical device. Background Technology
[0002] The high-nickel ternary lithium battery's energy density advantage makes it the mainstream choice for electric vehicles, but its poor thermal stability poses a significant safety hazard. Under thermal and electrical abuse, it is prone to chain exothermic reactions leading to thermal runaway. Existing safety technologies are mostly "single-point protection," which has limitations. To improve the safety of high-nickel ternary lithium batteries, existing technologies have proposed several improvement schemes, mainly including: (1) Electrolyte modification: Adding flame retardants improves battery safety, but it will damage electrochemical performance.
[0003] (2) Diaphragm and electrode coating: This method can only delay heat spread and cannot solve the problem of initial heat generation inside the electrode and at the interface.
[0004] (3) Modification of current collector: A coating layer, such as a carbon layer or a common ceramic layer, is formed on the current collector. However, this coating layer is prone to failure under high temperature and high voltage, or may react adversely with the active material.
[0005] In general, existing solutions typically improve battery safety through single measures, which have problems such as limited improvement effect, poor compatibility between components, and often at the expense of performance. Summary of the Invention
[0006] The purpose of this application is to provide a lithium battery and an electrical device to solve the above-mentioned problems.
[0007] To achieve the above objectives, this application adopts the following technical solution: A lithium battery includes a positive electrode and an electrolyte. The positive electrode includes a positive electrode current collector, a positive electrode active layer and a porous ceramic layer located on the positive electrode current collector, and the positive electrode active layer is located between the positive electrode current collector and the porous ceramic layer. The positive current collector includes an aluminum foil and an amorphous alloy coating on the aluminum foil; The positive electrode active layer comprises an oxide solid electrolyte, and the porous ceramic layer comprises a porous ceramic material and a lithium-ion conductor; The electrolyte is a locally high-concentration electrolyte or a gel-like quasi-solid electrolyte.
[0008] In some embodiments, the amorphous alloy coating is formed by a magnetron sputtering process; The sputtering target for the amorphous alloy coating includes Fe. 50 Cr 25 Al 25 Alloy or Fe60 Al 40 alloy.
[0009] In some embodiments, the method for preparing the amorphous alloy coating includes: placing an aluminum foil in the vacuum chamber of a PVD device and using Fe... 50 Cr 25 Al 25 Alloy or Fe 60 Al 40 Using the alloy as a sputtering target, argon and oxygen are introduced, with the oxygen partial pressure accounting for 20%-30% of the total gas pressure. The sputtering power is adjusted to 3-5 kW, the working gas pressure is 0.3-0.8 Pa, and the substrate temperature is controlled at 150-250℃. Magnetron sputtering reaction is carried out, and the deposition time is 30-170 minutes to form an amorphous alloy coating on the aluminum foil. And / or, the thickness of the amorphous alloy coating is 100-300 nm.
[0010] In some embodiments, the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (LATP); And / or, the D50 particle size of the oxide solid electrolyte is 100-500 nm; And / or, the positive electrode active layer is prepared by molding and drying a positive electrode slurry including an oxide solid electrolyte; And / or, the oxide solid electrolyte accounts for 0.5-10 wt% of the mass of the positive electrode slurry.
[0011] In some embodiments, the porous ceramic material includes at least one of alumina and zirconium oxide; And / or, the lithium-ion conductor comprises Li3PO4; And / or, the lithium-ion conductor accounts for 3%-10% of the total mass of the porous ceramic material and the lithium-ion conductor; And / or, the porous ceramic layer further includes a binder, the binder comprising polyvinylidene fluoride; And / or, in the porous ceramic layer, the mass ratio of the porous ceramic material to the lithium-ion conductor and the binder is (85-92):(5-8):(3-5); And / or, the thickness of the porous ceramic layer is 1~5 μm.
[0012] In some embodiments, the locally high-concentration electrolyte includes a lithium salt, a high dielectric constant solvent, and an inert diluent; The lithium salt includes lithium bis(fluorosulfonyl)imide; The high dielectric constant solvent includes at least one of acetonitrile, tetraethyl orthosilicate, and fluoroethylene carbonate. The inert diluent includes at least one of hydrofluoroether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethoxy(pentafluoro)cyclotriphosphatazole, fluorobenzene, and sulfolane. And / or, the method for preparing the locally high-concentration electrolyte includes: mixing the lithium salt with the high dielectric constant solvent to prepare a concentrated solution with a concentration of 2.5~4.5 mol / L; then adding the inert diluent to the concentrated solution so that the volume ratio of the high dielectric constant solvent to the inert diluent is 1:0.8~1:1.5, thereby obtaining the locally high-concentration electrolyte.
[0013] In some embodiments, the gel quasi-solid electrolyte comprises raw materials containing the following components, which are formed by in-situ polymerization: polymer monomers, lithium salts, solvents, photoinitiators, and plasticizers. And / or, the polymer monomer includes pentaerythritol tetraacrylate, the lithium salt includes LiFSI, the solvent includes fluoroethylene carbonate, the photoinitiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the plasticizer includes succinic acid nitrile; And / or, the concentration of the lithium salt is 1.5 ~ 5.0 mol / kg, whereby the concentration of the lithium salt refers to the ratio of the molar amount of the lithium salt to the total mass of the solvent and the plasticizer; And / or, the mass ratio of the polymer monomer to the solvent and the plasticizer is (8~12):(65~75):(18~25); And / or, the photoinitiator accounts for 0.2% to 5% of the mass of the polymer monomer; And / or, the preparation method of the gel quasi-solid electrolyte includes: mixing the polymer monomer, lithium salt, solvent, photoinitiator and plasticizer to obtain an electrolyte precursor solution; injecting the electrolyte precursor solution into a battery and irradiating it under ultraviolet light at a wavelength of 350~400 nm for 15~60 minutes to obtain a gel quasi-solid electrolyte.
[0014] In some embodiments, the battery further includes a separator; The membrane includes a base membrane and a functional layer located on the base membrane, the functional layer being located on the side closer to the positive electrode; And / or, the functional layer includes lithium iron phosphate, boron-doped zinc oxide and a binder, wherein the mass ratio of lithium iron phosphate to boron-doped zinc oxide is 6:4 to 8:2, and the mass ratio of the total mass of lithium iron phosphate and boron-doped zinc oxide to the mass of the binder is 90:10 to 95:5.
[0015] In some embodiments, the positive electrode active layer includes a positive electrode active material, which includes LiNi. 0.8 Co 0.1 Mn 0.1 O2; And / or, the battery further includes a negative electrode, the active material of which includes at least one of graphite, silicon-carbon composite material, lithium metal, and lithium metal composite material.
[0016] This application also provides an electrical device, including the lithium battery described above.
[0017] Compared with the prior art, the beneficial effects of this application include: 1. This application innovates from three dimensions: “material intrinsics (alloy coating current collector)”, “interface engineering (cathode composite and coating)”, and “dielectric essence (electrolyte)”, achieving a fundamental shift from “preventing heat spread” to “eliminating hot spots and ignition sources”, effectively improving battery safety.
[0018] 2. This application proposes an alloy-coated current collector, which effectively solves the problems of corrosion and high-temperature failure of aluminum foil.
[0019] This application employs a locally high-concentration or gel quasi-solid system, which combines the advantages of high safety (non-flammable, high voltage stability) and excellent electrochemical performance (high ionic conductivity, wide temperature range).
[0020] 3. The electrolyte of this application has high wettability and can fully penetrate into the interior of the positive electrode containing solid electrolyte particles to form a "liquid-solid" composite ion transport network, thereby improving rate performance.
[0021] The porous ceramic layer on the positive electrode surface of this application, combined with a non-flammable / flame-retardant electrolyte, can form a physically and chemically stable "passivation layer" on the positive electrode surface.
[0022] The alloy-coated current collector proposed in this application provides a stable and reliable current collection basis for the above system, avoiding the collapse of the entire electrode system due to current collector failure.
[0023] 4. The battery described in this application can pass rigorous tests such as hot box and overcharge, demonstrating high safety. Furthermore, due to optimized ion transport and a stable interface, it effectively improves the battery's cycle performance, particularly its cycle stability under high voltage.
[0024] 5. The processes described in this application (PVD coating, coating, and liquid injection) can all be upgraded and implemented on existing production lines. The material system has strong compatibility and has the potential for large-scale production. Detailed Implementation
[0025] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0026] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0027] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0028] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0029] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0030] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0031] A lithium battery includes a positive electrode and an electrolyte. The positive electrode includes a positive electrode current collector, a positive electrode active layer and a porous ceramic layer located on the positive electrode current collector, and the positive electrode active layer is located between the positive electrode current collector and the porous ceramic layer. The positive current collector includes an aluminum foil and an amorphous alloy coating on the aluminum foil; The positive electrode active layer comprises an oxide solid electrolyte, and the porous ceramic layer comprises a porous ceramic material and a lithium-ion conductor; The electrolyte is a locally high-concentration electrolyte or a gel-like quasi-solid electrolyte.
[0032] In some embodiments, the amorphous alloy coating is formed by a magnetron sputtering process; The sputtering target for the amorphous alloy coating includes Fe. 50 Cr 25 Al 25 Alloy or Fe 60 Al 40 alloy.
[0033] Amorphous alloy coatings possess the following characteristics: First, electrochemical inertness: within the battery operating voltage range (3.0-4.4V vs. Li... + Li is stable and does not participate in the reaction. Second, it has high corrosion resistance: effectively resisting corrosion from trace amounts of HF in the electrolyte. Third, it has excellent interfacial bonding and conductivity: it bonds firmly to the aluminum matrix and is itself conductive, ensuring electron transport. Fourth, it has high thermal stability: its melting point is much higher than that of aluminum, maintaining structural integrity under conditions of thermal abuse, preventing current collector melting and active material detachment, fundamentally eliminating the violent exothermic reaction at this interface.
[0034] In some embodiments, the method for preparing the amorphous alloy coating includes: placing an aluminum foil in the vacuum chamber of a PVD device and using Fe... 50 Cr 25 Al 25 Alloy or Fe 60 Al 40The alloy is used as the sputtering target. Argon and oxygen are introduced, with the oxygen partial pressure accounting for 20%-30% of the total gas pressure (e.g., 20%, 23%, 25%, 28%, 30%, or any value between 20% and 30%). The sputtering power is adjusted to 3-5 kW (e.g., 3 kW, 4 kW, 5 kW, or any value between 3 and 5 kW), and the working gas pressure is 0.3-0.8 Pa (e.g., 0.3 Pa, 0.5 Pa, 0.8 Pa, or 0.3-0.8 Pa). A magnetron sputtering reaction is performed with the substrate temperature controlled at 150-250℃ (e.g., 150℃, 180℃, 200℃, 230℃, 250℃ or any value between 150-250℃), and the deposition time is 30-170 minutes (e.g., 30 minutes, 50 minutes, 80 minutes, 100 minutes, 130 minutes, 150 minutes, 170 minutes or any value between 30-170 minutes) to form an amorphous alloy coating on the aluminum foil. The thickness of the amorphous alloy coating is 100-300 nm. For example, the thickness of the amorphous alloy coating is 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 230 nm, 250 nm, 280 nm, 300 nm or any value between 100-300 nm.
[0035] In some embodiments, the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; The positive electrode active layer of this application contains an oxide solid electrolyte, which can build an additional lithium-ion transport "highway" between active material particles, homogenize the current distribution, and reduce local polarization; at the same time, its high thermal stability can act as a "thermal stabilizer" to improve the overall thermal stability of the electrode.
[0036] The D50 particle size of the oxide solid electrolyte is 100-500 nm; The positive electrode active layer is prepared by molding and drying a positive electrode slurry including an oxide solid electrolyte. The oxide solid electrolyte in the positive electrode slurry has a mass percentage of 0.5-10 wt%. For example, the mass percentage of the oxide solid electrolyte in the positive electrode slurry can be 0.5 wt%, 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, or any value between 0.5-10 wt%.
[0037] In some embodiments, the positive electrode slurry further includes: 92 wt% - 97 wt% positive electrode active material, 1 wt% - 3 wt% conductive agent (including at least one of Super P and carbon nanotubes CNT), 1 wt% - 2 wt% binder (including polyvinylidene fluoride PVDF), 1-10 wt% oxide solid electrolyte and solvent (including N-methylpyrrolidone NMP), and the solid content of the positive electrode slurry is 65% - 75%.
[0038] For example, the content of positive electrode active material in the positive electrode slurry is any value between 92 wt%, 95 wt%, 97 wt%, or 92 wt% - 97 wt%; the content of conductive agent in the positive electrode slurry is any value between 1 wt%, 2 wt%, 3 wt%, or 1 wt% - 3 wt%; the content of binder in the positive electrode slurry is any value between 1 wt%, 2 wt%, or 1 wt% - 2 wt%; the content of oxide solid electrolyte in the positive electrode slurry is any value between 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, or 1-10 wt%; and the solid content of the positive electrode slurry is any value between 65%, 68%, 70%, 73%, 75%, or 65% - 75%.
[0039] In some embodiments, the porous ceramic material includes at least one of alumina and zirconium oxide; The lithium-ion conductor includes Li3PO4; The lithium-ion conductor accounts for 3%-10% of the total mass of the porous ceramic material and the lithium-ion conductor. For example, the lithium-ion conductor accounts for any value between 3%, 5%, 8%, 10% or 3%-10% of the total mass of the porous ceramic material and the lithium-ion conductor.
[0040] The porous ceramic layer also includes a binder, which includes polyvinylidene fluoride; In the porous ceramic layer, the mass ratio of porous ceramic material to lithium-ion conductor and binder is (85-92):(5-8):(3-5); For example, in a porous ceramic layer, the mass ratio of porous ceramic material to lithium-ion conductor and binder is any value between 85:5:3, 89:7:4, 92:8:5 or (85-92):(5-8):(3-5).
[0041] In some embodiments, the thickness of the porous ceramic layer is 1–5 μm. The porous ceramic layer acts as a "physical barrier," further reducing direct contact between the positive electrode and the electrolyte, and allowing selective passage of lithium ions.
[0042] For example, the thickness of the porous ceramic layer can be 1 μm, 3 μm, 5 μm, or any value between 1 and 5 μm.
[0043] In some embodiments, the method for preparing a porous ceramic layer includes: A functional coating slurry is provided, comprising a solid component and a solvent, wherein the solid component comprises, by mass percentage: 85%–92% porous ceramic material (e.g., any value between 85%, 88%, 90%, 92%, or 85%–92%), 5%–8% lithium-ion conductor (e.g., any value between 5%, 6%, 7%, 8%, or 5%–8%), and 3%–5% binder (e.g., any value between 3%, 4%, 5%, or 3%–5%); for example, the binder comprises polyvinylidene fluoride (PVDF), and the solvent is N-methylpyrrolidone, wherein the amount of solvent is such that the solid content of the functional coating slurry is 30%–40% (e.g., any value between 30%, 35%, 40%, or 30%–40%). The functional coating slurry is coated onto the surface of the positive electrode active layer and dried to obtain a porous ceramic layer. For example, the areal density of the functional coating slurry is 0.5~1.5 mg / cm³. 2 (e.g., 0.5 mg / cm) 2 1 mg / cm 2 1.5 mg / cm 2 Or 0.5~1.5 mg / cm 2 (any value between 80 and 120°C), drying includes drying at 80 to 120°C (e.g., 80°C, 100°C, 120°C or any value between 80 and 120°C) for 2 to 4 hours (e.g., 2 hours, 3 hours, 4 hours or any value between 2 and 4 hours).
[0044] In some embodiments, the locally high-concentration electrolyte includes a lithium salt, a high dielectric constant solvent, and an inert diluent; The lithium salt includes lithium bis(fluorosulfonyl)imide; The high dielectric constant solvent includes at least one of acetonitrile, tetraethyl orthosilicate, and fluoroethylene carbonate. The inert diluent includes at least one of hydrofluoroether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethoxy(pentafluoro)cyclotriphosphatazole, fluorobenzene, and sulfolane. Locally high-concentration electrolytes can form a special solvated sheath layer, easily forming a stable LiF-rich SEI film at the negative electrode, and exhibiting extremely high antioxidant decomposition ability (>4.5V) at the positive electrode, as well as high flash point and low volatility.
[0045] The method for preparing the locally high-concentration electrolyte includes: mixing the lithium salt with the high dielectric constant solvent to prepare a concentrated solution with a concentration of 2.5~4.5 mol / L (e.g., 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, or any value between 2.5~4.5 mol / L); then adding the inert diluent to the concentrated solution so that the volume ratio of the high dielectric constant solvent to the inert diluent is 1:0.8~1:1.5 (e.g., 1:0.8, 1:1, 1:1.2, 1:1.5, or any value between 1:0.8~1:1.5), to obtain the locally high-concentration electrolyte.
[0046] In some embodiments, the gel quasi-solid electrolyte comprises raw materials containing the following components, which are formed by in-situ polymerization: polymer monomers, lithium salts, solvents, photoinitiators, and plasticizers. The gel quasi-solid electrolyte has a gel network in which the solvent is locked within a three-dimensional polymer framework. This non-flowing electrolyte completely eliminates the risk of leakage and combustion, while maintaining good interfacial contact with the porous electrode.
[0047] The polymer monomer includes pentaerythritol tetraacrylate, the lithium salt includes LiFSI, the solvent includes fluoroethylene carbonate, the photoinitiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the plasticizer includes succinic acid nitrile. The concentration of the lithium salt is 1.5 to 5.0 mol / kg, and the concentration of the lithium salt refers to the ratio of the molar amount of the lithium salt to the total mass of the solvent and the plasticizer; for example, the concentration of the lithium salt is 1.5 mol / kg, 2 mol / kg, 2.5 mol / kg, 3 mol / kg, 3.5 mol / kg, 4 mol / kg, 4.5 mol / kg, 5 mol / kg or any value between 1.5 and 5.0 mol / kg.
[0048] The mass ratio of the polymer monomer to the solvent and the plasticizer is (8~12):(65~75):(18~25); for example, the mass ratio of the polymer monomer to the solvent and the plasticizer is any value between 8:65:18, 10:70:22, 12:75:25 or (8~12):(65~75):(18~25).
[0049] The photoinitiator accounts for 0.2% to 5% of the mass of the polymer monomer; for example, the photoinitiator accounts for any value between 0.2%, 1%, 3%, 5% or 0.2% to 5% of the mass of the polymer monomer.
[0050] The preparation method of the gel quasi-solid electrolyte includes: mixing the polymer monomer, lithium salt, solvent, photoinitiator, and plasticizer to obtain an electrolyte precursor solution; injecting the electrolyte precursor solution into a battery and irradiating it under ultraviolet light at a wavelength of 350~400 nm (e.g., 350 nm, 360 nm, 370 nm, 380 nm, 390 nm, 400 nm or any value between 350~400 nm) for 15~60 minutes (e.g., 15 minutes, 30 minutes, 60 minutes or any value between 15~60 minutes) to obtain the gel quasi-solid electrolyte.
[0051] In some embodiments, the battery further includes a separator; The separator includes a base membrane and a functional layer located on the base membrane, the functional layer being located on the side closer to the positive electrode; The functional layer comprises lithium iron phosphate, boron-doped zinc oxide, and a binder. The mass ratio of lithium iron phosphate to boron-doped zinc oxide is 6:4 to 8:2, and the mass ratio of the total mass of lithium iron phosphate and boron-doped zinc oxide to the mass of the binder is 90:10 to 95:5. Lithium iron phosphate acts as a "heat buffer," absorbing heat through a phase transition during localized overheating. Boron-doped zinc oxide possesses excellent thermal conductivity and electronic insulation, enabling uniform heat dissipation and preventing lithium dendrite penetration.
[0052] For example, the mass ratio of lithium iron phosphate to boron-doped zinc oxide is 6:4, 7:3, 8:2 or any value between 6:4 and 8:2; the mass ratio of the total mass of lithium iron phosphate and boron-doped zinc oxide to the mass of the binder is 90:10, 92:8, 95:5 or any value between 90:10 and 95:5.
[0053] In some embodiments, the base film is a polyethylene / polypropylene composite nonwoven fabric base film with a thickness of 9 μm.
[0054] In some embodiments, the method for preparing the diaphragm includes: Lithium iron phosphate and boron-doped zinc oxide were mixed at a mass ratio of 7:3 to obtain an inorganic mixture; the inorganic mixture was then dispersed with polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) binder at a mass ratio of 92:8 in a solvent (e.g., N-methylpyrrolidone NMP), with the solid content controlled at 25%, to obtain a coating slurry; The coating slurry is applied to one side of the base film; The coated base film was initially dried at 60°C, and then vacuum dried at 100°C for 12 hours to obtain a composite functional membrane.
[0055] In some embodiments, the thickness of the functional layer is 1.5-2.5 μm. For example, the thickness of the functional layer is 1.5 μm, 2 μm, 2.5 μm, or any value between 1.5 and 2.5 μm.
[0056] In some embodiments, the positive electrode active layer includes a positive electrode active material, which includes LiNi. 0.8 Co 0.1 Mn 0.1 O2; The battery also includes a negative electrode, the active material of which includes at least one of graphite, silicon-carbon composite material, lithium metal, and lithium metal composite material.
[0057] This application also provides an electrical device, including the lithium battery described above.
[0058] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0059] Example 1 Example 1 provides a lithium-ion battery, the preparation method of which includes: (1) Current collector preparation: Aluminum foil with a thickness of 12μm is selected, and the surface oil is removed by ultrasonic cleaning with acetone and ethanol in sequence. Then, it is sputtered by argon ions to activate the surface.
[0060] The pretreated aluminum foil was placed in the vacuum chamber of a physical vapor deposition (PVD) apparatus, and the back vacuum of the chamber was evacuated to 5.0 × 10⁻⁶. -3 Below Pa. Using Fe 50 Cr 25 Al 25 The alloy was used as a sputtering target. Argon and oxygen were introduced, and under the conditions of oxygen partial pressure of 25%, substrate temperature of 200℃, sputtering power of 4 kW and working pressure of 0.55 Pa, it was deposited on a cleaned 12μm aluminum foil for 150 minutes to form a FeCrAlO alloy coating with a thickness of 200 nm on the aluminum foil, which was then used as the positive electrode current collector.
[0061] (2) Preparation of positive electrode: Positive electrode slurry: 96.5 wt% NCM811, 1.5 wt% Super P, 1.5 wt% PVDF, and 0.5 wt% LATP nanoparticles (Li). 1.3 Al 0.3 Ti 1.7 (PO4)3) was mixed with NMP to prepare a positive electrode slurry with a solid content of 70%.
[0062] Coating: The positive electrode slurry is coated onto the positive electrode current collector prepared in step (1), with a single-sided coating areal density of 20 mg / cm². 2 It is dried at 120℃ and rolled to a compacted density of 3.4 g / cm³. 3 A positive electrode active layer is formed on the positive electrode current collector.
[0063] Surface coating: 91 wt% ZrO2, 6 wt% Li3PO4 (Li3PO4 accounts for 6.2 wt% of the total mass of ZrO2 and Li3PO4), 3 wt% PVDF and NMP were mixed to obtain a slurry with a solid content of 35%, which was then coated on the surface of the positive electrode active layer with a single-sided coating areal density of 1.0 mg / cm³. 2 The cathode is then dried in an oven at 100°C for 3 hours to form a porous ceramic layer with a thickness of 3μm.
[0064] (3) Electrolyte: A local high-concentration electrolyte is used.
[0065] In an argon-filled glove box (H2O, O2 < 0.1 ppm), LiFSI (lithium bisfluorosulfonylimide) was added to FEC (fluoroethylene carbonate) and stirred at 60°C until completely dissolved, yielding a clear concentrate with a concentration of 3.5 mol / L. After cooling to room temperature, TTE (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) was slowly added to achieve a FEC to TTE volume ratio of 1:1.2. The mixture was stirred until homogeneous, resulting in a locally high-concentration electrolyte.
[0066] (4) Preparation of diaphragm: The coating slurry composition is as follows: Lithium iron phosphate (LiFePO4) powder and boron-doped zinc oxide (ZnO:B, boron doping amount 1at%) powder are mixed at a mass ratio of 7:3, and then dispersed in N-methylpyrrolidone (NMP) with polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) binder at a mass ratio of 92:8 (inorganic matter: binder). The solid content is controlled at 25% to obtain the coating slurry.
[0067] Coating process: The above coating slurry is coated on one side of a polyethylene / polypropylene (PE / PP) composite nonwoven fabric base film with a thickness of 9μm using a micro-gravure coating method.
[0068] Drying and parameters: The membrane was initially dried at 60℃, and then vacuum dried at 100℃ for 12 hours to obtain the composite functional membrane. The single-sided coating thickness of the membrane was 2μm, and the porosity was approximately 45%.
[0069] Battery assembly: Using graphite as the negative electrode, and employing the above-mentioned positive electrode sheet, composite functional separator, and electrolyte, small-capacity soft-pack batteries are assembled in an argon glove box.
[0070] Example 2 Example 2 provides a lithium-ion battery, the preparation method of which includes: (1) Current collector preparation: Aluminum foil with a thickness of 12μm is selected, and the surface oil is removed by ultrasonic cleaning with acetone and ethanol in sequence. Then, it is sputtered by argon ions to activate the surface.
[0071] The pretreated aluminum foil was placed in the vacuum chamber of a physical vapor deposition (PVD) apparatus, and the back vacuum of the chamber was evacuated to 5.0 × 10⁻⁶. -3 Below Pa. Using Fe 60 Al 40 Using the alloy as a sputtering target, argon and oxygen were introduced, and under the conditions of oxygen partial pressure of 20%, substrate temperature of 180℃, sputtering power of 3.5 kW and working pressure of 0.5 Pa, an Fe-Al-O alloy coating (thickness of 180 nm) was deposited on aluminum foil, which was then used as the positive electrode current collector.
[0072] (2) Preparation of positive electrode: Same as in Example 1.
[0073] (3) Electrolyte: Gel quasi-solid electrolyte is used.
[0074] Composition and proportions: Polymer monomer: Pentaerythritol tetraacrylate (PET4A), with a mass ratio of polymer monomer to solvent and plasticizer of 10:70:20.
[0075] Lithium salt: LiFSI.
[0076] Solvent: Fluoroethylene carbonate (FEC).
[0077] Photoinitiator: 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), accounting for 1% of the polymer monomer (PET4A) by mass.
[0078] Plasticizer: Butadionitrile (SN).
[0079] Preparation: In a glove box, LiFSI was dissolved in a mixed solvent of FEC and SN at a concentration of 3.0 mol / kg. The concentration of LiFSI refers to the ratio of the molar amount of LiFSI to the total mass of FEC and SN. Then, PET4A monomer and HMPP initiator were added, and the mixture was stirred until a homogeneous and transparent electrolyte precursor solution was formed.
[0080] (4) Separator and battery assembly: The preparation method of the separator is the same as in Example 1.
[0081] The positive electrode, separator, and graphite negative electrode are stacked to form a battery cell, which is then packaged in an aluminum-plastic film bag, injected with an electrolyte precursor solution, and vacuum-sealed. After being irradiated under 365 nm ultraviolet light for 30 minutes, in-situ solidification is completed to form a gel quasi-solid electrolyte. After formation and aging, a small-capacity soft-pack battery is obtained.
[0082] Comparative Example 1 The lithium-ion battery in Comparative Example 1 uses ordinary aluminum foil, conventional positive electrode slurry, ordinary LiPF6 / EC-DEC electrolyte, and conventional separator.
[0083] Current collector: Ordinary 12μm aluminum foil (uncoated).
[0084] Positive electrode preparation: The positive electrode slurry does not contain LATP and its composition is NCM811, Super P, and PVDF, with a mass ratio of 96.5:1.5:2.0. No porous ceramic layer is prepared after the formation of the positive electrode active layer. The remaining processes are the same as in Example 1.
[0085] Electrolyte: Conventional electrolyte, specifically a 1.0 M LiPF6 EC / EMC mixed solution with a volume ratio of EC to EMC of 3:7.
[0086] Separator: PE / PP composite nonwoven fabric base membrane, 9μm thick, and uncoated.
[0087] Comparative Example 2 Alloy-coated aluminum foil and conventional electrolyte were used, otherwise the same as in Example 1.
[0088] Current collector: Aluminum foil with FeCrAlO alloy coating as in Example 1.
[0089] Positive electrode preparation: Same as Comparative Example 1, i.e., the positive electrode active layer does not contain LATP, and the surface of the positive electrode active layer does not have a porous ceramic layer.
[0090] Electrolyte: The same conventional electrolyte as in Comparative Example 1.
[0091] Diaphragm: Same as the ordinary diaphragm in Comparative Example 1.
[0092] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that 12μm aluminum foil was used as the current collector, and the surface of the aluminum foil had no FeCrAlO alloy coating. Everything else was the same as in Example 1.
[0093] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the step of preparing the porous ceramic layer is omitted after the formation of the positive electrode active layer. Everything else is the same as in Example 1.
[0094] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the positive electrode slurry does not contain LATP, and its composition is NCM811, Super P, and PVDF, with a mass ratio of 96.5:1.5:2.0. Everything else is the same as in Example 1.
[0095] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the positive electrode slurry does not contain LATP, and its composition is NCM811, Super P, and PVDF in a mass ratio of 96.5:1.5:2.0. Furthermore, no porous ceramic layer is prepared after the formation of the positive electrode active layer. Everything else is the same as in Example 1.
[0096] Comparative Example 7 The only difference between Comparative Example 7 and Example 1 is that the diaphragm uses a common PE / PP composite nonwoven fabric base film with a thickness of 9 μm and no coating. Everything else is the same as in Example 1.
[0097] Effect verification: 1. Testing method: Cycle performance: The battery was charged at 0.5C constant current to 4.3V at 25℃, then switched to constant voltage until the current dropped to 0.05C, and then discharged at 0.5C constant current to 3.0V. The discharge capacity of the first and 300th cycles was recorded, and the capacity retention rate was calculated.
[0098] Thermal stability test: The fully charged (4.3V) battery was placed in a programmable temperature control chamber and heated to 150°C at a heating rate of 5°C / min and held for 1 hour. The surface temperature and appearance of the battery were monitored.
[0099] Overcharge test: At 25℃, the battery is overcharged at a constant current of 1C until the voltage reaches 10V. Observe whether thermal runaway occurs. If thermal runaway does not occur, record the highest temperature on the battery surface.
[0100] 2. The test results are shown in Table 1. Table 1. Performance Test Comparison Table of Examples and Comparative Examples
[0101] Cyclic performance: The high capacity retention of Examples 1-2 is due to the completely conventional Comparative Example 1. It benefits from the uniform current distribution of LATP and the stable interface film formed by the modified electrolyte, which proves that the scheme of this application has an improving effect on cyclic performance.
[0102] Thermal stability test: In Examples 1-2, the temperature remained stable at 150~151℃, and the cell appearance was intact, proving that the battery of this application has high high-temperature resistance and can effectively improve the battery's safety performance. Comparative Example 1 caught fire and exploded, indicating that the high-temperature resistance of the completely conventional solution is poor. Comparative Examples 2-7 did not experience thermal runaway, but the battery surface temperature was slightly higher than 150℃ (152~158℃), accompanied by varying degrees of bulging, indicating that the lack of a single improvement can lead to a decrease in thermal stability.
[0103] Overcharge Test: Examples 1-2 showed no thermal runaway, had the lowest cell surface temperature, and exhibited significantly better safety performance than Comparative Examples 1-7. Comparative Examples 1 and 6 experienced thermal runaway, demonstrating that a completely conventional approach or the lack of multiple improvements can lead to poor safety performance. Comparative Example 2 experienced thermal runaway, emitting smoke but not catching fire, proving that the alloy coating provides some protection, but its use alone is insufficient to completely suppress overcharge thermal runaway. Comparative Examples 3-5 and 7 did not experience thermal runaway, but the highest surface temperature of their batteries was higher than that of Examples 1-2, demonstrating that all improvements contributed to the safety performance.
[0104] Examples 1-2 performed best in all tests, demonstrating that the proposed solution can effectively improve the cycle performance and safety performance of the battery. Comparative Examples 3-7 all showed varying degrees of safety degradation when one improvement was missing. Comparative Example 6 (missing two positive electrode modifications) experienced thermal runaway during overcharge testing, while Comparative Examples 4-5 (missing only one modification) did not experience thermal runaway, demonstrating a synergistic effect between the positive electrode slurry LATP and the surface coating. Comparative Example 2 (alloy coating only + conventional electrolyte) experienced thermal runaway and smoked but did not ignite during overcharge, while Example 1 (alloy coating + modified electrolyte) did not experience thermal runaway, demonstrating the necessity of their synergistic effect.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0106] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A lithium battery, characterized in that, It includes a positive electrode and an electrolyte. The positive electrode includes a positive electrode current collector, a positive electrode active layer and a porous ceramic layer located on the positive electrode current collector, and the positive electrode active layer is located between the positive electrode current collector and the porous ceramic layer. The positive current collector includes an aluminum foil and an amorphous alloy coating on the aluminum foil; The positive electrode active layer comprises an oxide solid electrolyte, and the porous ceramic layer comprises a porous ceramic material and a lithium-ion conductor; The electrolyte is a locally high-concentration electrolyte or a gel-like quasi-solid electrolyte.
2. The lithium battery according to claim 1, characterized in that, The amorphous alloy coating is formed by magnetron sputtering. The sputtering target for the amorphous alloy coating includes Fe. 50 Cr 25 Al 25 Alloy or Fe 60 Al 40 alloy.
3. The lithium battery according to claim 2, characterized in that, The method for preparing the amorphous alloy coating includes: placing aluminum foil in the vacuum chamber of a PVD device, and using Fe... 50 Cr 25 Al 25 Alloy or Fe 60 Al 40 Using the alloy as a sputtering target, argon and oxygen are introduced, with the oxygen partial pressure accounting for 20%-30% of the total gas pressure. The sputtering power is adjusted to 3-5 kW, the working gas pressure is 0.3-0.8 Pa, and the substrate temperature is controlled at 150-250℃. Magnetron sputtering reaction is carried out, and the deposition time is 30-170 minutes to form an amorphous alloy coating on the aluminum foil. And / or, the thickness of the amorphous alloy coating is 100-300 nm.
4. The lithium battery according to claim 1, characterized in that, The oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3; And / or, the positive electrode active layer is prepared by molding and drying a positive electrode slurry including an oxide solid electrolyte; And / or, the oxide solid electrolyte accounts for 0.5-10 wt% of the mass of the positive electrode slurry.
5. The lithium battery according to claim 1, characterized in that, The porous ceramic material includes at least one of alumina and zirconium oxide; And / or, the lithium-ion conductor comprises Li3PO4; And / or, the lithium-ion conductor accounts for 3%-10% of the total mass of the porous ceramic material and the lithium-ion conductor; And / or, the porous ceramic layer further includes a binder, the binder comprising polyvinylidene fluoride; And / or, in the porous ceramic layer, the mass ratio of the porous ceramic material to the lithium-ion conductor and the binder is (85-92):(5-8):(3-5); And / or, the thickness of the porous ceramic layer is 1~5μm.
6. The lithium battery according to claim 1, characterized in that, The localized high-concentration electrolyte includes lithium salt, a high dielectric constant solvent, and an inert diluent; The lithium salt includes lithium bis(fluorosulfonyl)imide; The high dielectric constant solvent includes at least one of acetonitrile, tetraethyl orthosilicate, and fluoroethylene carbonate. The inert diluent includes at least one of hydrofluoroether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethoxy(pentafluoro)cyclotriphosphatazole, fluorobenzene, and sulfolane. And / or, the method for preparing the locally high-concentration electrolyte includes: mixing the lithium salt with the high dielectric constant solvent to prepare a concentrated solution with a concentration of 2.5~4.5 mol / L; then adding the inert diluent to the concentrated solution so that the volume ratio of the high dielectric constant solvent to the inert diluent is 1:0.8~1:1.5, thereby obtaining the locally high-concentration electrolyte.
7. The lithium battery according to claim 1, characterized in that, The gel quasi-solid electrolyte is formed by in-situ polymerization of raw materials containing the following components: polymer monomers, lithium salts, solvents, photoinitiators, and plasticizers; And / or, the polymer monomer includes pentaerythritol tetraacrylate, the lithium salt includes LiFSI, the solvent includes fluoroethylene carbonate, the photoinitiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the plasticizer includes succinic acid nitrile; And / or, the concentration of the lithium salt is 1.5 ~ 5.0 mol / kg, whereby the concentration of the lithium salt refers to the ratio of the molar amount of the lithium salt to the total mass of the solvent and the plasticizer; And / or, the mass ratio of the polymer monomer to the solvent and the plasticizer is (8~12):(65~75):(18~25); And / or, the photoinitiator accounts for 0.2% to 5% of the mass of the polymer monomer; And / or, the preparation method of the gel quasi-solid electrolyte includes: mixing the polymer monomer, lithium salt, solvent, photoinitiator and plasticizer to obtain an electrolyte precursor solution; injecting the electrolyte precursor solution into a battery and irradiating it under ultraviolet light at a wavelength of 350~400nm for 15~60 minutes to obtain a gel quasi-solid electrolyte.
8. The lithium battery according to claim 1, characterized in that, The battery also includes a separator; The separator includes a base membrane and a functional layer located on the base membrane, the functional layer being located on the side closer to the positive electrode; And / or, the functional layer includes lithium iron phosphate, boron-doped zinc oxide and a binder, wherein the mass ratio of lithium iron phosphate to boron-doped zinc oxide is 6:4 to 8:2, and the mass ratio of the total mass of lithium iron phosphate and boron-doped zinc oxide to the mass of the binder is 90:10 to 95:
5.
9. The lithium battery according to any one of claims 1-8, characterized in that, The positive electrode active layer includes a positive electrode active material, which includes LiNi. 0.8 Co 0.1 Mn 0.1 O2; And / or, the battery further includes a negative electrode, the active material of which includes at least one of graphite, silicon-carbon composite material, lithium metal, and lithium metal composite material.
10. An electrical-related device, characterized in that, Including the lithium battery as described in any one of claims 1-9.
